Memahami Praktik Kepemimpinan Suku Jawa: Studi Kasus Manajer Jawa Timur di PT XYZ, Jakarta - puspita, angela candra; Heikal, Jerry (Journal of Entrepreneurship, Management and Industry (JEMI), 2023)
Leadership is an activity of moving and influencing the people around them, each leader has their own style for leading a scope. In this research, researchers review Javanese leadership, especially the East Java region. The research objective is to analyse leadership practices, document Javanese cultural norms and values that influence leadership, and understand how Javanese cultural traditions and leadership practices can be integrated into modern business dynamics. The method of this research uses ethnographic methods. Researchers looked for sources of information from interviews with 4 manager respondents from East Java at PT XYZ, Jakarta. From the interview results, it was found that cultural values influence the management strategy of how East Java managers manage teams and problem solving management strategies in the dynamics of modern business